Testing of weak form efficiency on Bursa Malaysia’s selected indexes / W Nurliana Aida W Mhd Kamal - W Mhd Kamal, W Nurliana Aida (Faculty of Business and Management, 2018)
The purpose of this study is to investigate the existence of Efficient Market Hypothesis (EMH) in Bursa Malaysia’s selected indexes. However, this study is only testing the weak form of EMH. The indexes chosen for this research is Emas, Mids Cap, Small Cap and Top 100 Index. The data was collected in for each index for daily basis from year 2013 to 2017. This study used Autoregressive Model to regress the previous return index with the current return index. Tests employed for this study includes descriptive analysis, test for estimated empirical model, stationary tests and diagnostic tests. Result of this study reveals that for daily data, all of the indexes have significant relationship which can be concluded as inefficiently weak. All the data for indexes can be concluded as inefficiently weak. These results provide understanding towards investors, analysts and regulator in dealing with Efficient Market Hypotheses.